Evaluation of World Bank programs in Afghanistan 2002-11 (Independent Evaluation Group Studies, 2013)
Chapter Abstracts Chapter 1 This chapter examines the country context, including continuing conflict and insecurity, poverty, and the role of development partners and non-state actors (civil society and humanitarian organizations) in Afghanistan. It examines coming transitions in security arrangements, including political and economic transitions. It outlines the evaluation methods used, as well as limitations. Chapter 2 This chapter deals with the World Bank Group strategy and program, the Bank Group's operational program, portfolio performance, analytic and advisory activities review, the Afghanistan Reconstruction Fund, and the new Interim Strategy Note, as well as previous Transitional Support Strategies and ISNs. Chapter 3 This chapter examines the building of state capacity and state accountability to its citizens, specifically issues such as results and shortcomings in public financial management, public sector governance, and health and education. The World Bank Group contribution is highlighted. Risks to development outcomes are discussed. Chapter 4 This chapter examines the issue of promoting growth in the rural economy and improving rural livelihoods, including sectors such as rural roads, agriculture and water. The National Solidarity Program and the Bank Group?s contribution to it are discussed. Risks to development outcomes are noted. Chapter 5 This chapter concerns support for the formal private sector, examining the overall investment climate and financial sector. It looks at possibilities for growth in the mining and hydrocarbons sector, information and communications technology, and power sectors. Urban development is also examined. The World Bank Group contribution is highlighted. Chapter 6 This chapter provides an overall assessment (relevance, efficacy) of the Bank Group?s program in Afghanistan, outlining the internal and external drivers of success (knowledge services, staff capacity, customization of program design to country context, alignment of donor objectives, etc) and weakness. Chapter 7 This chapter outlines the lessons for fragile and conflict-affected situations drawing on the specifics of the Afghanistan evaluation case. Recommendations are offered in areas such as labor markets, human resources, strategic-level analytical work vis-a-vis long-term development strategies, and strengthening of the regulatory environment for private sector investment.